Evaluasi Program Jaminan Kesehatan Nasional (JKN) dalam Penyelenggaraan Pelayanan Kesehatan di Kecamatan Negara, Kabupaten Jembrana - Damayanti, Ni Komang Intan Tri; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER; Vol 3 No 1 (2023): Administrasi Publik 2023, 2023)
Jembrana Regent Regulation Number 31 of 2017 concerning the Implementation of the Employment and Health Social Security Program serves as a reference or basis for clarifying the Implementation of the National Health Insurance Program (JKN) in the Implementation of Health Services in the State District, Jembrana Regency. The implementation of the JKN program in state sub-districts has internal and external constraints. Informant Determination Techniques in this study using purposive sampling. Based on this research study using the theory of the evaluation criteria according to William N. Dunn (2012) with indicators of Effectiveness, Efficiency, Adequacy, Equitable, Responsiveness, and Constancy. Keywords: National Health Insurance, Program Evaluation, State Distric